Identifikasi Daerah Interes Calon Tapak PLTN Kalimantan Barat Berdasarkan Kriteria Umum - Suntoko, Hadi (BRIN Publishing, 2014)
Identification of interesting areas for the nuclear power plant site in general based on natural conditions and human activities has been carried out. The guidelines of International Atomic Energy Agency (IAEA) safety guide NS-R-3,(2003) concerning Site Evaluation, that the scope of study includes a regional, near regional, site vicinit, site area and assessment in West Kalimantan is regionally, includes Singkawang City, Bengkayang, Pontianak City, Pontianak Regency, Sanggau, Sekadau, Kubu Raya, North Kayong and Ketapang. The purpose of identify is to obtain interesting areas around the coastal region ± 3km to landward based on swamp conditions, the thickness of the peat, chemical industry, gas pipeline/oil, sea ports, river demarcation line, military sites, nature reserves/cultural/wildlife refuges, and population density. The methods used are description, identification, interpretation of secondary data and confirmation of a finite field, analyzed based on general criteria. Identification results obtained interesting areas includes Dekan Putih (Meliau-Sanggau), Kubu (Kubu Raya), Sukadana (North Kayong), Tempurukan (Ketapang).